A comparative study of linear, Y-shaped and linear-dendritic methoxy poly(ethylene glycol)-block-polyamidoamine-block-poly(l-glutamic acid) block copolymers for doxorubicin delivery in vitro and in vivo. (August 2016) - Zhang, Yu; Xiao, Chunsheng; Ding, Jianxun; Li, Mingqiang; Chen, Xin; Tang, Zhaohui; Zhuang, Xiuli; Chen, Xuesi
Graphical abstract: Abstract: The linear, Y-shaped, and linear-dendritic block copolymers of methoxy poly(ethylene glycol)- block -polyamidoamine- block -poly(l -glutamic acid) (MPEG- b -PAMAM- b -PGA) with one, two, four, and eight PGA arms but similar MPEG/PGA weight ratios ( W / W ) (named as P1PA, P2PA, P4PA and P8PA, respectively) were synthesized and comparatively investigated for doxorubicin hydrochloride (DOX) delivery. All the obtained block copolymers were highly biocompatible and could efficiently load DOX into nanoparticles (NPs) through electrostatic interaction. The NPs formed by linear (P1PA) or Y-shaped (P2PA) block copolymers and DOX were spherically shaped with smaller sizes, while the NPs formed from linear-dendritic block copolymers (P4PA and P8PA) were irregular in shape and larger in size. The P1PA/DOX and P2PA/DOX NPs exhibited better DOX protection and slower DOX release profile. However, cell cytotoxicity assays indicated that all the DOX-loaded NPs exhibited similar cytotoxicities with free DOX, indicating effective DOX release after cellular uptake. The NPs from linear and Y-shaped block copolymers greatly extended the blood circulation time, and displayed more accumulation in tumor site and less accumulation in the liver and kidney compared with the linear-dendritic counterparts. In addition, the P1PA/DOX and P2PA/DOX NPs also exhibited higher anti-tumor efficacy and less toxicity than the other DOX formulations. All these results indicated that the linear and Y-shaped MPEG- b -PAMAM- b -PGA block copolymers displayed better DOX delivery ability in anti-tumor treatment than the linear-dendritic copolymers. Statement of Significance: Polymeric NPs derived from block copolymers have emerged as effective vehicles for drug delivery. However, the majority of the researches in this field have involved simple linear block copolymers and there are very few comparative studies on the self-assembly, in vitro, and in vivo drug delivery by the block copolymers with similar composition but different architectures. In this study, a series of linear, Y-shaped, and linear-dendritic polypeptide-based block copolymers were prepared and thoroughly investigated for DOX delivery. These block polymers loaded DOX into NPs with different sizes and morphologies, and exhibited different anti-tumor capabilities both in vitro and in vivo . The results indicated that the architecture of the block copolymers played an important role in their drug delivery behaviors.